KEPUASAN PENGGUNA SISTEM INFORMASI AKADEMIK (SIAKAD ONLINE) DI FKIP UNS DAN PENGARUHNYA TERHADAP MANFAAT PENINGKATAN KUALITAS PEMBELAJARAN - Dona Kristiawan; Sunarto Sunarto; Muhammad Sabandi (Department of Economics Education, Universitas Sebelas Maret, 2018)
The purpose of this study was to determine: 1) the effect of quality systems on student satisfaction. 2) influence the quality of information on student satisfaction. 3) the effect of service quality on student satisfaction. 4) the effect of the benefits of user satisfaction in learning. This research is a survey. The study population is students of Economics Faculty of Education Teacher Training And Education Univerisitas March Surakarta. Samples were taken by proportional random sampling technique. The research data obtained by questionnaire. The validity of the data carried by the internal validity. Analysis of the data used in this research is the analysis of structural equation models. The conclusion of this study were: 1) There is a significant effect on the quality of the system of student satisfaction. 2) There is a significant effect the quality of information on student satisfaction. 3) There is a significant effect of service quality on student satisfaction. 4) There is a significant influence of satisfaction on the benefits of learning.